2023
DOI: 10.1128/mra.01340-22
|View full text |Cite
|
Sign up to set email alerts
|

Complete PacBio Single-Molecule Real-Time Sequence of a Novel Probiotic-Like Bacterium, Rouxiella badensis subsp. acadiensis , Isolated from the Biota of Wild Blueberries in the Acadian Forest

Abstract: The PacBio whole-genome sequencing of the potential probiotic strain Canan SV-53T recovered from lowbush blueberries demonstrates high homology to Rouxiella badensis but with distinct enough clusters to propose the name Rouxiella badensis subsp. acadiensis . The sequencing also detected the presence of two native plasmids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Of note, Gram (-) probiotic bacteria such as Escherichia coli Nissle 1917 have been largely studied over the years. This new potential probiotic strain has been demonstrated by genomic prediction completed by the National Research Council of Canada (NRC) and by in vitro studies, not to show virulence genes nor resistance to antibiotics [ 24 ]. The authors also demonstrated its ability to resist the adverse conditions encountered during its passage through the intestinal tract following oral administration [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, Gram (-) probiotic bacteria such as Escherichia coli Nissle 1917 have been largely studied over the years. This new potential probiotic strain has been demonstrated by genomic prediction completed by the National Research Council of Canada (NRC) and by in vitro studies, not to show virulence genes nor resistance to antibiotics [ 24 ]. The authors also demonstrated its ability to resist the adverse conditions encountered during its passage through the intestinal tract following oral administration [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…62/916,921 entitled “Probiotics Composition and Methods” for its potential probiotic effects, was provided by Chantal Matar from the University of Ottawa. The strain was isolated from blueberry microbiota [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%